2009
DOI: 10.1007/s00586-009-1157-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety of thoracic pedicle screw application using the funnel technique in Asians: a cadaveric evaluation

Abstract: The objective of this cadaveric study is to determine the safety and outcome of thoracic pedicle screw placement in Asians using the funnel technique. Pedicle screws have superior biomechanical as well as clinical data when compared to other methods of instrumentation. However, misplacement in the thoracic spine can result in major neurological implications. There is great variability of the thoracic pedicle morphometry between the Western and the Asian population. The feasibility of thoracic pedicle screw ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…36,[39][40][41][42][43][44][45][46] Despite none of the perforations caused screw-related complications in this study, there were a grade 2 medial perforation which may result in neurologic complications and a grade 2 as well as a grade 3 ( Figure 3) anterior perforation which may risk injury to mediastinal visceral structures. O'Brien et al 47 had reported a case of oesophageal injury after instrumentation of the T3 vertebrae due to backward pressure from the endotracheal tube and trachea that pushed the oesophagus unto the tip of the anterior perforated screws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,[39][40][41][42][43][44][45][46] Despite none of the perforations caused screw-related complications in this study, there were a grade 2 medial perforation which may result in neurologic complications and a grade 2 as well as a grade 3 ( Figure 3) anterior perforation which may risk injury to mediastinal visceral structures. O'Brien et al 47 had reported a case of oesophageal injury after instrumentation of the T3 vertebrae due to backward pressure from the endotracheal tube and trachea that pushed the oesophagus unto the tip of the anterior perforated screws.…”
Section: Discussionmentioning
confidence: 99%
“…McLain et al 12 found that at T4, 61% of pedicles were too small, at T5, 67% were too small and at T6, 75% were too small to accept a 5.5-mm screws from dissection of 18 human cadavers. Others had documented the narrowest pedicle width was located at T4 [33][34][35] or at T5 15,[36][37][38] which may subject them to higher risks of perforation. In our study, we found that there was a peak in the perforation rate at T4 (14.0%) and T6 (14.5%).…”
Section: Discussionmentioning
confidence: 99%
“…По другим данным [29], количество мальпозиций в грудном отделе достигает 31,6 %, в пояснич-ном -10,6 %. До 48,0 % мальпозиций в грудном отделе приходится на уро-вень Th 1 -Th 6 , что обусловлено мень-шим диаметром ножек позвонков [6]. Около 56 % некорректно установлен-ных винтов располагается на вогну-той стороне деформации [2], что мож-но объяснить структурной диспла-зией дужек и апикальной торсией.…”
Section: рисunclassified
“…Наиболее надежными являются транспедикулярные системы, требую-щие точной установки винтов в тела позвонков через корни дужек. Транс-педикулярная фиксация позволяет выполнять трехплоскостную коррек-цию деформаций с фиксацией трех колонн позвоночника, сохраняя мак-симальное количество позвоночно-двигательных сегментов [1,6,7,11,14,15,25,30]. Несмотря на очевидные преимущества транспедикулярной фиксации, ее широкое распростра-нение ограничено риском невроло-гических и сосудистых осложнений из-за мальпозиции винтов [7,14,36,40,43,46].…”
unclassified
“…There had been evidences that showed differences in the thoracic pedicle morphometry between Caucasians and Asians [22][23][24] which may alter the feasibility or safety of percutaneous pedicle screw technique among Asians. Therefore, this study was done to directly compare the safety of fluoroscopic guided percutaneous thoracic pedicle screw placement between Caucasians and Asians.…”
Section: Introductionmentioning
confidence: 99%